IMPLEMENTATION OF THE SIMPLE MULTI-ATTRIBUTE RATING TECHNIQUE (SMART) METHOD FOR SUPPORT SELECTION OF COFFEE SHOP BUSINESS LOCATION - Viola Alfheny; Ali Ibrahim (Jurnal Teknik Informatika (Jutif), 2022)
In choosing a business location, a computerized system is needed and can provide effective and accurate information about the business location. Many young entrepreneurs today are starting to try to manage and create a coffee shop business, so the competition in coffee shops is very high. The high competition in the coffee shop business makes it difficult for prospective tenants to determine the most appropriate location to establish a place of business according to their desired needs. In addition, the selection of business locations cannot be chosen arbitrarily because it can cause a shortage of visitors which results in the coffee shop being deserted. Therefore, choosing a strategic place using several criteria is needed to support business success. There are twelve criteria that will be used, the criteria are rental price, number of competitors, parking area, cleanliness, building area, supporting business, road distance, road access, population density, pedestrian traffic, population income, and the center of the crowd. This study aims to help prospective tenants who will open a place of business in the city of Bandar Lampung. The method used in this research is the Simple Multi Attribute Rating Technique (SMART). The SMART method is used because it is a multi-attribute decision-making method where the alternative consists of a set of criteria, with weights to determine how important one criterion is with another. The results obtained in this study are a decision support system for choosing a strategic coffee shop business location, making it easier for prospective tenants to choose the right business location for the development of a coffee shop business in Bandar Lampung.